Implementación de un sistema de costos por procesos en la florícola “Paramo Roses” ubicada en el barrio colcas, parroquia Mulalo, ciudad Latacunga, en la provincia de Cotopaxi, en el periodo de mayo-junio 2015 - León Quinteros, Mireya Paola (2015)
This research was developed up, the research has for objectives to maximize the benefits of the same to optimizes the resources, materials and production spending, giving an added to value the product to obtain the total satisfaction of the clients, allowing to get an image with quality, health and innovation of the flower plantation. It was recommended the implementation a system of process costs for the flower plantation ¨PARAMO ROSES¨ the same will allow and help to determine with accuracy the real value of the product in each process taking into account the reduction of raw material, workforce and indirect manufacturing costs, being the most important factors to calculate the unit cost of production. This system allows to control the suitable management of the different stages of the process for the desired product, given as a result the increase of profitability, productivity in the market and for a better decision making in benefit of itself. Financial states are presented according to the structure of the IFRS showing actual made movements fulfilled during a stablished period, they will help to interpret and analyses, the current economic situation of the flower plantation.